2018
DOI: 10.1002/stem.2751
|View full text |Cite
|
Sign up to set email alerts
|

Concise Review: Cell Therapy for Critical Limb Ischemia: An Integrated Review of Preclinical and Clinical Studies

Abstract: Critical limb ischemia (CLI), the most severe form of peripheral artery disease, is characterized by pain at rest and non-healing ulcers in the lower extremities. For patients with CLI, where the extent of atherosclerotic artery occlusion is too severe for surgical bypass or percutaneous interventions, limb amputation remains the only treatment option. Thus, cell-based therapy to restore perfusion and promote wound healing in patients with CLI is under intense investigation. Despite promising preclinical studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
197
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(201 citation statements)
references
References 119 publications
(142 reference statements)
1
197
1
2
Order By: Relevance
“…MSCs have been used for myocardial infarction therapy and ischemic limb treatment [1, 9396]. Studies have shown that MSCs can improve cardiac function, and promote vascularization in ischemic limbs [1, 9396]. The major contribution of MSCs lies in their paracrine effects which provide multiple growth factors necessary for cell survival and angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MSCs have been used for myocardial infarction therapy and ischemic limb treatment [1, 9396]. Studies have shown that MSCs can improve cardiac function, and promote vascularization in ischemic limbs [1, 9396]. The major contribution of MSCs lies in their paracrine effects which provide multiple growth factors necessary for cell survival and angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The major contribution of MSCs lies in their paracrine effects which provide multiple growth factors necessary for cell survival and angiogenesis. These growth factors include but are not limited to IGF-1, HGF, bFGF, VEGF, and PDGF [1, 9396]. Approaches that stimulate MSC paracrine effects are attractive as they may increase therapeutic efficacy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After the purification, precipitates were vacuum dried at room temperature (20-30 °C). As the gelatin sample control, original ApGltn (Org-ApGltn) was also synthesized without adding hexanal and 2-picBH 3 . The modification ratio of the hexyl group was quantified by the TNBS method, [24][25][26] comparing absorbance between Organd C6-ApGltn.…”
Section: Synthesis and Characterization Of C6-apgltnmentioning
confidence: 99%
“…We believe that the present report can serve as a reference for future studies on novel therapeutic interventions that would enhance collateral growth. For example, a porcine model could help in the optimization of delivery methods, dosing and efficacy testing of experimental arteriogenic treatments, including cell-based therapies [23,[25][26][27][28].…”
Section: Both Ligation Versions Induced a Similar Amount Of Ischemia mentioning
confidence: 99%